Association between Brain-Derived Neurotrophic Factor and Lipid Profiles in Acute Ischemic Stroke Patients - Tuwar, Mayuri N.; Chen, Wei-Hung; Yeh, Hsu-Ling; Bai, Chyi-Huey (International journal of molecular sciences, 2024)
Ischemic stroke, the most prevalent form of stroke, leads to neurological impairment due to cerebral ischemia and affects 55–90% of the population. Brain-derived neurotrophic factor (BDNF) plays a crucial role in the central nervous system and regulates cardiometabolic risk factors, including lipids. This single-center study aimed to explore the relationship between lipid profiles and BDNF levels in 90 patients who had experienced AIS for the first time. The results show that the high BDNF group (≥3.227 ng/mL) had significantly higher HbA1C and TG levels; ratios of TC/HDL-C, LDL-C/HDL-C, and TG/HDL-C; and percentage of hyperlipidemia (60%) as well as lower levels of HDL-C, with an OR of 1.903 (95% CI: 1.187–3.051) for TG/HDL-C, 1.975 (95% CI: 1.188–3.284) for TC/HDL-C, and 2.032 (95% CI: 1.113–3.711) for LDL-C/HDL-C. Plasma BDNF levels were found to be significantly positively correlated with TG and negatively with HDL-C, with OR values of 1.017 (95% CI: 1.003–1.030) and 0.926 (95% CI: 0.876–0.978), respectively. TC/HDL-C, TG/HDL-C, and LDL-C/HDL-C ratios are associated with BDNF levels in AIS patients. The results also indicate that, in AIS patients, higher BDNF levels are associated with lower HDL and higher TG concentrations.